Association between ALDH2 rs671 polymorphism and risk of ischemic stroke: A protocol for systematic review and meta analysis. Issue 21 (22nd May 2020) - Jiang, Yan; He, Jinting; Liu, Hongyu; Xu, Zhongxin
Abstract : Abstract: In last decades, many scholars have studied the relationship between aldehyde dehydrogenase 2 ( ALDH2 ) rs671 and ischemic stroke (IS), however, the results obtained from these studies were inconclusive. The purpose of this study was to investigate the association between rs671 and the risk of IS by systematically review. Two researchers independently screened relevant published literatures, derived data and estimated the risk of bias of the research in Pubmed, Embase, Ovid, China National Knowledge Infrastructure (CNKI), Cochrane Library and China Biomedical Literature Database throughout March 29, 2020. All statistical analyses were performed with the Stata 12.0 software. The data of the study was analyzed using fixed and random effects models. The results were expressed by odds ratio (OR) and 95% confidence interval (95%CI). A total of 10 articles were included this study. The total number of samples for all studies was 5265, including 2762 cases and 2503 controls. Statistical results indicated statistical differences between ALDH2 rs671 polymorphism and IS under dominant model (AA vs. AG + GG) and allelic model (A vs G), ORs (95% CI) were 1.66 (1.27–2.17) ( P  = .00) and 1.34 (1.05–1.71) ( P  = .02), respectively. But there was no statistical difference under recessive model (AA + AG vs GG), OR (95% CI) was 1.40 (0.99–1.97), P  = .06. ALDH2 rs671 polymorphism was related to IS risk for Chinese population and the A allele of rs671 may be a risk factor of IS.